Master-controlled networking for mobile robotic application - Nga, Jia Jun (2023)
This project focuses on developing a low-cost, IoT-based, master-controlled networking system for swarm robotic cars. With the use of the NodeMCU v2 ESP8266 microcontroller, the role of each robotic car can be defined as either a master or slave. Consequently, the slave robotic cars can connect to the master's soft access point and establish a wireless communication channel with each other. This robot-to-robot communication is vital in modern smart industries, as it can significantly increase productivity and efficiency. To incorporate human-to-robot communication, a simple and easy-to-use mobile application has been developed that allows the user to send primary motion orders to the master robotic car and control the network connectivity of the slaves. In addition, the developed robotic cars can perform obstacle avoidance using their ultrasonic sensors to detect obstacles. The micro servo motor enables them to rotate the sensing direction of the ultrasonic sensor, allowing them to sense obstacles on their left or right side. Moreover, the robotic cars can automatically change their pattern formation to a line if a narrow hallway is detected, and return to their default pattern formation once they have passed through the narrow pathway. A well-implemented communication session will be established between the master and slave robotic cars before deciding on a change in the pattern formation. Furthermore, the robotic cars use the light-dependent resistor to measure the brightness of their environment and switch their LED on or off accordingly. The NodeMCU v2 ESP8266 microcontroller is the main component of this project and is programmed to control the remaining key components, including the L298N motor driver, SG90 servo motor, HC-SR04 ultrasonic sensor, and light-dependent resistor. The software involved in the development of this robotic application includes the Arduino IDE and ESP8266WiFi library.